2016
DOI: 10.15407/mining10.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of watering filled-up rock massif on geomechanical stability of the cyclic and progressive technology line

Abstract: Purpose. Comprehensive assessment of the fill slope stability for cyclical-and-continuous technology (CCT) conveyors applied to rocks of stripping at Pervomaiskiy quarry of PJSC "Severnyi GOK" to justify effective antilandslide measures. Methods.To study geomechanical stability of fill-up rock mass and slopes of the CCT line, the following methods are used: hydrogeological analysis, visual observation of the object, numerical modeling of the fill slope stability in the finite element analysis software Phase2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The use of appropriate levels and gradations of the stability of natural and man-made slopes is a key element in the evaluation and forecasting of their landslide hazard. Regarding geotechnical objects of openpit mining of minerals, the known scales of the values of the safety factors for slopes and pit walls, as well as dump arrays are used [14]. To evaluate the stability of natural slopes, such a gradation of the landslide hazard levels is absent.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of appropriate levels and gradations of the stability of natural and man-made slopes is a key element in the evaluation and forecasting of their landslide hazard. Regarding geotechnical objects of openpit mining of minerals, the known scales of the values of the safety factors for slopes and pit walls, as well as dump arrays are used [14]. To evaluate the stability of natural slopes, such a gradation of the landslide hazard levels is absent.…”
Section: Research Resultsmentioning
confidence: 99%
“…As a result of numerical simulation, it is found that in homogeneous slopes without attenuation surfaces, significant deformations are practically absent with a SF ≥ 1.5 [14,15]. This state of the soft rock massif is objectively characterized as the most stable, therefore, the landslide hazard level is «low», which makes it possible to assign this position to the I class of hazard level according to the proposed scale.…”
Section: Research Resultsmentioning
confidence: 99%
“…The influence of well-known laws of mechanics is manifested in the conditions of borehole hydromining (BHM). They are expressed in the manifestation of the balance law of mining pressure work, the results of which, in the conditions of hydraulic mining, are proportional to the loss of minerals in the subsoil [17]. Based on this, the main task of mountain pressure management is to maximize the share of work that goes to the safe deformation of the massif outside the excavation chambers, and to minimize it -to the deformation of the roof and protective units.…”
Section: Development Of a Methodology For Calculating The Parameters ...mentioning
confidence: 99%
“…To model the process of softening of tuff-stone, it is of considerable interest to determine the analytical type of dependence on which the dehydration process takes place. Sample № 7 was taken for the study as the most characteristic for dump tuff-stone [15][16][17]. The analytical dependence of the species was established, and it is assumed that this dependence reduces the mass of the sample over time during dehydration.…”
Section: Methodsmentioning
confidence: 99%